Continuous phase stabilization and active interferometer control using two modes - Jotzu, G; Bartley, T; Coldenstrodt-Ronge, H; Smith, B; Walmsley, I (2012)
We present a computer-based active interferometer stabilization method that can be set to an arbitrary phase difference and does not rely on modulation of the interfering beams. The scheme utilizes two orthogonal modes propagating through the interferometer with a constant phase difference between them to extract a common relative phase and generate a linear feedback signal. Switching times of 50ms over a range of 0-6π radians at 632.8 nm are experimentally demonstrated. The relative interferometer phase can be stabilized up to several days to within ± 3°. © 2011 Copyright Taylor and Francis Group, LLC.